Performance analysis of piezoelectric energy harvesting system employing bridgeless power factor correction boost rectifier. (2021) - Jai Ganesh, R.; Kodeeswaran, S.; Kavitha, M.; Ramkumar, T.
Abstract: Nowadays piezoelectric generators play an important role in self-powered systems for charging many low powered wireless and portable electronic components thus not limited by finite battery energy. The present work describes the reliable modeling of piezoelectric transducer driven by mechanical input and a power conversion circuit to harvest maximum energy. Lead Zirconate Titanium (LZT) based transducer and Zero Current Switching (ZCS) Power Factor Correction (PFC) Bridgeless Boost (BLB) Rectifier both combined together forms an efficient energy harvesting system. LZT cantilevered based generator with tip mass of 1 g/m 2 is modeled to capture ambient vibration energy and convert into usable energy to create self-powering system. In the proposed work BLB rectifier reduces switching stress which in turn reduces switching losses considerably. Furthermore, switches used in the current pathway are also bargain while compared to existing system Separate control strategy is worn to get better power factor. A detailed analysis of piezoelectric generator employing BLB power factor correction converter topology along with control strategy is presented herein. The performance of energy harvesting system and output of PFC bridgeless boost rectifier are obtained by using MATLAB software package and the results are validated.